ROBOT2013: First Iberian Robotics Conference Advances in Robotics, Vol.2 - Armada, Manuel A; Sanfeliu, Alberto; Ferre, Manuel (Advances in Intelligent Systems and Computing, 2014)
The interest in robotics has remarkably augmented over recent years. Novel solutions for complex and very diverse application fields (exploration/intervention in severe environments, assistive, social, personal services, emergency rescue operations, transportation, entertainment, unmanned aerial vehicles, medical, etc.), has been anticipated by means of a large progress in this area of robotics. Moreover, the amalgamation of original ideas and related innovations, the search for new potential applications and the use of state of the art supporting technologies permit to foresee an important step forward and a significant socio-economic impact of advanced robot technology in the forthcoming years. In response to the technical challenges in the development of these sophisticated machines, a significant research and development effort has yet to be undertaken. It concerns embedded technologies (for power sources, actuators, sensors, information systems), new design methods, adapted control techniques for highly redundant systems, as well as operational and decisional autonomy and human/robot co-existence.   This book contains the proceedings of the ROBOT 2013: FIRST IBERIAN ROBOTICS CONFERENCE and it can be said that included both state of the art and more practical presentations dealing with implementation problems, support technologies and future applications. A growing interest in Assistive Robotics, Agricultural Robotics, Field Robotics, Grasping and Dexterous Manipulation, Humanoid Robots, Intelligent Systems and Robotics, Marine Robotics, has been demonstrated by the very relevant number of contributions. Moreover, ROBOT2013 incorporates a special session on Legal and Ethical Aspects in Robotics that is becoming a topic of key relevance. This Conference will be held in Madrid (28-29 November 2013), organised by the Sociedad Española para la Investigación y Desarrollo en Robótica (SEIDROB) and by the Centre for Automation and Robotics - CAR (Universidad Politécnica de Madrid (UPM) and Consejo Superior de Investigaciones Científicas (CSIC)), along with the co-operation of Grupo Temático de Robótica CEA-GTRob, Sociedade Portuguesa de Robotica  (SPR), and Asociación Española de Promoción de la Investigación en Agentes Físicos (RedAF).